THE SEMANTIC CLASSIFICATION OF ANIMAL SYMBOLS IN ENGLISH (Ustozlar uchun, 2026)
This article examines the semantic classification of animal symbols in English, focusing on how specific animals acquire metaphorical, cultural, and emotional meanings. The study identifies major semantic categories such as positivity, negativity, intelligence, strength, and peace, and analyzes how these symbolic meanings appear in proverbs, idioms, and common expressions. By exploring the cultural background behind animal symbolism, the article provides insights into how English speakers conceptualize human traits and social behavior through animals.